Building a smart surface with converse temperature-dependent wettability based on poly(acrylamide-co-acrylonitrile). Issue 19 (18th February 2020) - Chen, Longbin; Yang, Tao; Niu, Yue; Mu, Xin; Gong, Yelei; Feng, Yancong; de Rooij, Nicolaas Frans; Wang, Yao; Li, Hao; Zhou, Guofu
Abstract : A sensitive, adjustable, and reversible smart surface with converse temperature-dependent wettability was constructed from an upper critical solution temperature-type copolymer. Abstract : A smart surface with converse temperature-dependent (CTD) wettability was fabricated from an upper critical solution temperature-type (UCST-type) poly(acrylamide- co -acrylonitrile) (P(AAm- co -AN)) copolymer. The obtained surface exhibits a remarkable and reversible hydrophobic–hydrophilic transition depending on temperature with a high response rate. The static water contact angle of the surface decreases from 103° ± 2° to 60° ± 1° as the temperature increases from 30 °C to 80 °C. Further, the wettability of the UCST-type surface shows a positive linear relationship between wettability and temperature. This study for the first time provides an UCST-type smart surface with wettability that decreases by over 35° as the temperature increases by only 20 °C.